Biological Characterization and Clinical Value of OAS Gene Family in Pancreatic Cancer - Gao, Li-Juan; Li, Jia-Lei; Yang, Rui-Rui; He, Zhong-Mei; Yan, Min; Cao, Xia; Cao, Ji-Min (Frontiers in Oncology, 2022)
Background: OAS gene family plays an important role in antiviral process, but its role in pancreatic cancer has not yet been studied. Methods: We analyzed the expression, prognostic value and biological function of the OAS gene family in human pancreatic cancer through comprehensive bioinformatic analysis and cellular level validation. Results: Results showed that OAS family was highly expressed in pancreatic cancer, and this high expression significantly affected the clinical stage and prognosis of the tumor. OAS gene family was closely related to the immune infiltration of pancreatic cancer, especially neutrophils and dendritic cells, and many immune-related factors and pathways are enriched in the tumor, such as type I interferon signaling pathway and NOD-like receptor signaling pathway. Conclusion: Taken together, high expression of OAS family is closely related to poor prognosis of pancreatic cancer. OAS gene family may serve as the biomarker and even therapeutic target of pancreatic cancer.